Cadmium tolerance in tomato: determination of organ-specific contribution by diallel analysis using reciprocal grafts - Lupp, Renata Mota; Marques, Deyvid Novaes; Lima Nogueira, Marina [UNESP]; Carvalho, Marcia Eugenia Amaral; Azevedo, Ricardo Antunes; Piotto, Fernando Angelo (Springer Nature, 2024)
Given the increasing problems of water and soil contamination with cadmium (Cd), it is necessary to investigate the genetic and physiological mechanisms of tolerance to this metal in different crops, which can be used for the development of effective crop management strategies. This study aimed to assess the potential of grafting as a strategy to increase Cd tolerance and reduce absorption in tomato by evaluating the contribution of the root system and aerial parts for tolerance mechanisms. To this end, reciprocal grafting and diallel analyses were used to examine the combining ability of contrasting tomato genotypes under exposure to 0 and 35 µM CdCl2. Roots and above-ground parts were found to have specific mechanisms of Cd tolerance, absorption, and accumulation. Grafting of the USP15 genotype (scion) on USP16 (rootstock) provided the greatest synergism, increasing the tolerance index and reducing the translocation index and Cd accumulation in leaves. USP163 exhibited potential for breeding programs that target genotypes with high Cd tolerance. In tomato, both Cd tolerance and accumulation in aerial parts are genotype- and tissue-specific, controlled by a complex system of complementary mechanisms that need to be better understood to support the development of strategies to reduce Cd contamination in aerial parts.
Keywords: Accessions; Biomass accumulation; Cadmium; Combining ability; Diallel analysis; Heavy metals; Solanum lycopersicum L.; Tolerance index